PENGARUH LATIHAN DRILLS MENGGIRING BOLA TERHADAP KEMAMPUAN DRIBBLING TEAM U-15 SSB BINTANG SEROJA KOTA DUMAI - Reyhan Arsuwando; Ni Putu Nita Wijayanti; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the effect of dribbling drills training on the dribbling ability of the U15 Ssb Bintang Seroja Dumai soccer team. The research was carried out in the soccer field at SSB Bintang Seroja, Jl. Cut Nyak Dien, Purnama, Dumai Barat, Dumai City on July 13, 2020. The population in this study were the SSB players of Bintang Seroja Dumai with a total sample of 12 athletes who participated in training at Ssb Bintang Seroja Dumai. Before the analysis was carried out, first a pre-test was carried out with an average result of 18.39, then carried out through the training of dribbling during 16 meetings with 12 players of SSB Rajawali Pekanbaru and the average post-test result was 16.80. . Based on the statistical t-test analysis, the difference value is obtained at 1.59 and produces a t count of 9.93 and a t table of 1.79. Means titung> t table. It can be concluded that drills training in dribbling has an effect on dribbking ability. Based on the results of data analysis it can be concluded as follows: that dribbling training (X) has an influence on dribbling ability (Y) in the SSB Bintang Seroja Dumai Team.Key Words: Effect of Drill Training, Dribbling Ability